IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 9 TAHUN 2013 TENTANG PENGATURAN PASAR TRADISIONAL DI KOTA SEMARANG - Wahyu Savitri; Turtiantoro .; Sulityowati . (Journal of Politic and Government Studies, 2015)
Abstract:The existence of traditional market in Semarang City has weakened along the growth of the development of the modern market which is rapidly increasing. Its function as an economic generator, the Semarang City Government needs to be more responsive on the existence of traditional market as a supporter of public economic activities and revenue by increasing the retribution. On that account, the Government has made changes to the Regulation No.9/2013 on the traditional market setting replace the old regulations. This study used a qualitative research method with descriptive type. The results showed that the Semarang City Regulation No.9/2013 of Traditional Market has not been realized optimally. This can be seen in the work programs that is executed slowly and misdirected; lack of facilities and infrastructure to regulate traditional markets; lack of good HR policy implementers and the absence of guidance to the merchant; and lack of utilization technology facilities, causing services are less than optimal. Some of the above shortcomings have complained by traders which are not in accordance with the billing fees that always exceed the target realization.Keywords: Implementation, Regional Regulation, Traditional Market.